2019
DOI: 10.1002/jpln.201800339
|View full text |Cite|
|
Sign up to set email alerts
|

Nutrient flows and balances in intensively managed vegetable production of two West African cities

Abstract: This study reports and analyzes nutrient balances in experimental vegetable production systems of the two West African cities of Tamale (Ghana) and Ouagadougou (Burkina Faso) over a two‐year period comprising thirteen and eleven crops, respectively. Nutrient‐use efficiency was also calculated. In Tamale and Ouagadougou, up to 2% (8 and 80 kg N ha−1) of annually applied fertilizer nitrogen were leached. While biochar application or wastewater irrigation on fertilized plots did not influence N leaching in both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In the 20t/ha -1 biochar treatment, biochar amendment could have sustained soil P availability for coffee seedling uptake [32].…”
Section: Discussionmentioning
confidence: 99%
“…In the 20t/ha -1 biochar treatment, biochar amendment could have sustained soil P availability for coffee seedling uptake [32].…”
Section: Discussionmentioning
confidence: 99%
“…These comprised maize, cabbage ( Brassica oleracea L.), amaranth ( Amaranthus cruentus ), lettuce ( Lactuca sativa L.), jute mallow ( Corchorus olitorius L.), and roselle ( Hibiscus sabdariffa L.; Tab. ; Akoto‐Danso et al., , ; Werner et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown the agronomic benefits of waste water and biochar application in UPA system of Tamale ( Werner et al., ; Akoto‐Danso et al., ). Biochar application enhanced N‐use efficiency on fertilized plots, while N surpluses were higher when the crops were irrigated with waste water ( Akoto‐Danso et al., ). To better understand the nutrient dynamics in intensively managed UPA systems and to derive and test‐implement sustainable management options, which minimize nutrient losses, further research is required.…”
Section: Introductionmentioning
confidence: 99%
“…It contributes to sequester carbon into the soil and improves soil properties to reduce greenhouse gas emissions (Lehmann, 2007;Laird et al, 2010;Collet and Rousseau, 2015;Naisse, 2015). Other studies show a beneficial effect of biochar on soil fertility and plant productivity when combined with fertilizer or manure (Novak et al, 2009;Badji, 2011;Xu et al, 2012;Manka'abusi et al, 2019;Akoto-Danso et al, 2019;Lompo et al, 2020).…”
Section: Introductionmentioning
confidence: 95%